The relation between different phases of sprint run and specific strength parameters of lower limbs - Cunha, L. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The sprint is determined by the ability to accelerate, the magnitude of maximal velocity and the ability to maintain velocity against the onset of fatigue. For the sprint coach it is important to have objective information concerning horizontal velocity, in the different phases of sprinting and the key mechanisms to these different phases. The aim of our study is to examine the relationships between the different phases of 100m sprinting and the results obtained with different tests, where we quantify the capability to produce force in isometric, and stretch shortening cycle (SSC) contraction modes. The inexistence of correlation between different phases of sprint, and the tests seem hard to explain. Different explanation could be given.